Micromechanics of hemp strands in polypropylene composites - Vallejos, María Evangelina (2012)
The present paper investigates micromechanics of hemp strands. The main objective of the present work has been the determination of the intrinsic strength of hemp strands. Hemp strands have been used as reinforcement of Polypropylene composites. Different percentages of hemp strands and coupling agents (MAPP) have been tested to obtain a map of the mechanical properties of that kind of composites and the effect of the components on the final properties. Mechanical properties of the different specimens have been tested using standard experimental methods and equipment. Micromechanics of the strands have been obtained using Hirsch model, Bowyer-Bader methodology and Kelly-Tyson model.